Perubahan Fungsi Ruang Taneyan Lanjhang Pada Masyarakat Migran Madura Di Desa Krajan Jember - Ridjal, Abraham Mohammad (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2014)
1Exodus by Madurese people to Java, represented one of the resident disseminating process in Indonesia. Besides transfer of human beings, there were also architecture and culture transfer, especially house remain was important shares in human life. The aim of this architecture’s research is to know changes of architecture that happened in two cultures in its life pattern. Though culture that goes on it follows local culture, however its architecture’s orientation does not stem from the same culture, and so does on the contrary. This matter represent there are values that able to perceive physically on the elements of architecture, and also its influence on its pattern habit of society exist in depth.This research represents a kind of study and object case research, by determining one of the research object and conduct it with in depth study to get required data to analyse. Besides, this research also represents a qualitative research to describe and compare of two architectures. In course of analysis, quantitative data also needed, which obtained from questioner concerning architecture composition. By the existence of existing change and difference gotten after analysis process by compare of two architecture, showed that architecture have a dynamically character. Besides, the change and its dynamically was supported by a very good relationship between architecture, human being and environment where the architecture woke up.Keywords: Madurese architecture, culture, environment